Imperfect Competition in the Recycling Industry - Thomas Eichner (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2003)
This paper studies the market allocation in an economy where material is used for producing a consumption good, then recycled and finally landfilled, and where a recycling firm has market power. The material content constitutes an aspect of green product design and affects the recycling costs. Although the recycling firm's supply of recycling services is inefficiently low, she does not abuse her market power to distort the product design allocation. Different policy schemes are proposed which correct for market failures. One promising candidate is a relative recycling standard combined with a consumption good's tax, a material subsidy and a subsidy on recycling services.
Keywords: H21; L12; Q28; 330; imperfect competition; recycling; product design; Kreislaufwirtschaft; Abfallwirtschaft; Unvollkommener Wettbewerb; Produktdesign; Öko-Produkt; Steuerpolitik; Subvention; Theorie